Dehydroepiandrosterone (DHEA) reduces embryo aneuploidy: direct evidence from preimplantation genetic screening (PGS) - Weghofer Andrea; Gleicher Norbert; Barad David H (BMC, 2010)
Abstract Background Dehydroepiandrosterone (DHEA) has been reported to improve pregnancy chances in women with diminished ovarian reserve (DOR), and to reduce miscarriage rates by 50-80%. Such an effect is mathematically inconceivable without beneficial effects on embryo ploidy. This study, therefore, assesses effects of DHEA on embryo aneuploidy. Methods In a 1:2, matched case control study 22 consecutive women with DOR, supplemented with DHEA, underwent preimplantation genetic screening (PGS) of embryos during in vitro fertilization (IVF) cycles. Each was matched by patient age and time period of IVF with two control IVF cycles without DHEA supplementation (n = 44). PGS was performed for chromosomes X, Y, 13, 16, 18, 21 and 22, and involved determination of numbers and percentages of aneuploid embryos. Results DHEA supplementation to a significant degree reduced number (P = 0.029) and percentages (P < 0.001) of aneuploid embryos, adjusted for relevant covariates. Short term supplementation (4-12 weeks) resulted in greatest reduction in aneuploidy (21.6%, 95% CI -2.871-46.031). Discussion Beneficial DHEA effects on DOR patients, at least partially, are the likely consequence of lower embryo aneuploidy. DHEA supplementation also deserves investigation in older fertile women, attempting to conceive, where a similar effect, potentially, could positively affect public health.